Aplicação conjunta do custeio baseado em atividades com o valor econômico agregado (EVA) em uma cooperativa agropecuária avícola de corte. - Souza Filho, Men de Sá Moreira de (2007)
The present work aims a joint application of Activity Based Costing (ABC) with Economic Value Added (EVA) in a poultry agropecuary cooperative. Firstly, it was defined the following for the development of the model of Activity Based Costing (ABC) as part of cooperative productive chain: poultry slaughterhouse, feed industry, incubatoty and broiler parents farm. Secondly, it was evaluated the economic value creation at the cooperative through the Economic Value Added (EVA) indicator. Finally, joint application of Activity Based Costing (ABC) with Economic Value Added (EVA) was performed for costing objects of feed industry and poultry slaughterhouse cooperatives products. As result of the research, it was identified the following: cooperative products costing in terms of activities, evaluation of the value creation in the cooperative and cooperative products costing was possible based in activities, evaluation of value creation in the cooperative and which products create or destroy economic value in this organization. The model of Activity Based Costing (ABC) was applied for costing of cost objects in the operational units of the cooperative. The results showed evidencing in the case of the poultry slaughterhouse unit the presence of products with negative margin and rentability. Regards to the application of EVA it was verified that the cooperative presented a creation of economic value in the three last years of the carried through evaluation, however with one raised level of dependence of external capital for operations development. The joint application of Activity Based Costing (ABC) with Economic Value Added (EVA) revealed viable with regard to its use in the structure of the poultry slaughterhouse and feed industry by means of the use drivers of capital cost. This application assists in the evaluation and adequacy of products mix of the cooperative for direction the value creation.